2017
DOI: 10.1021/acsenergylett.7b00844
|View full text |Cite
|
Sign up to set email alerts
|

Interdigitated Eutectic Alloy Foil Anodes for Rechargeable Batteries

Abstract: An interdigitated eutectic alloy (IdEA) foil is presented as a framework for the development of alloy anodes with a capacity that is significantly higher than that of the traditional graphite/copper assembly. It is a simple, low-cost approach that can be applied to a broad range of alloy systems with various working ions such as Li, Na, or Mg.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…5 Given the complexity and diversity of electrodes investigated in the literature, it is critical that researchers provide measurements of lithiated electrode thickness rather than relying upon theoretically calculated values. [6][7][8][9][10][11][12][13][14] Understanding electrode-level performance is further complicated by the tendency to report capacities normalized to the weight of the active material, discounting the binder and copper current collector. While these inactive components make up only 7% of the volume of a graphite electrode, they can make up $20% of state-of-the-art silicon systems.…”
Section: Context and Scalementioning
confidence: 99%
See 3 more Smart Citations
“…5 Given the complexity and diversity of electrodes investigated in the literature, it is critical that researchers provide measurements of lithiated electrode thickness rather than relying upon theoretically calculated values. [6][7][8][9][10][11][12][13][14] Understanding electrode-level performance is further complicated by the tendency to report capacities normalized to the weight of the active material, discounting the binder and copper current collector. While these inactive components make up only 7% of the volume of a graphite electrode, they can make up $20% of state-of-the-art silicon systems.…”
Section: Context and Scalementioning
confidence: 99%
“…2,16 The Interdigitated Eutectic Alloy (IdEA) anode framework, first described by our group, utilizes a simple rolling mill to produce nanostructured electrodes. 6 Metal alloys are plastically deformed by extensive cold-rolling, elongating them in the rolling direction and refining them in the transverse dimension. When this technique is applied to two-phase metal alloys, the resulting foil morphology is that of interdigitated sub-micron domains of the two constituent phases.…”
Section: Context and Scalementioning
confidence: 99%
See 2 more Smart Citations
“…They concluded that the poor cycle life is related to an inability to completely remove all the inserted lithium. Recently, an interdigitated eutectic alloy including Sn and aluminum (Al) has been developed as a high capacity anode [21].…”
Section: Introductionmentioning
confidence: 99%